Enantiomeric resolution and X-ray optical activity of a tricobalt extended metal atom chain. Issue 5 (13th December 2017) - Srinivasan, Anandi; Cortijo, Miguel; Bulicanu, Vladimir; Naim, Ahmad; Clérac, Rodolphe; Sainctavit, Philippe; Rogalev, Andrei; Wilhelm, Fabrice; Rosa, Patrick; Hillard, Elizabeth A.
Abstract : Enantiopure single crystals of extended metal atom chains display exceptionally large optical X-ray dichroisms at the Co K-edge. Abstract : A simple procedure based on anion exchange was employed for the enantiomeric resolution of the extended metal atom chain (EMAC) [Co3 (dpa)4 (MeCN)2 ] 2+ . Use of the chiral salt (NBu4 )2 [As2 (tartrate)2 ], (Λ-1 or Δ-1 ), resulted in the selective crystallization of the EMAC enantiomers as [Δ-Co3 (dpa)4 (MeCN)2 ](NBu4 )2 [Λ-As2 (tartarte)2 ]2, (Δ-2 ) and [Λ-Co3 (dpa)4 (MeCN)2 ](NBu4 )2 [Δ-As2 (tartrate)2 ]2 (Λ-2 ), respectively, in the P 421 2 space group, whereas a racemic mixture of1 yielded [Co3 (dpa)4 (MeCN)2 ][As2 (tartrate)2 ]·2MeCN ( rac -3 ), which crystallized in the C 2/ c space group. The local electronic and magnetic structure of the EMAC enantiomers was studied, exploiting a variety of dichroisms in single crystals. A strong linear dichroism at the Co K-edge was observed in the orthoaxial configuration, whereas it vanished in the axial orientation, thus spectroscopically confirming the D 4 crystal symmetry. Compounds Δ-2 and Λ-2 are shown to be enantiopure materials as evidenced by mirror-image natural circular dichroism spectra in the UV/vis in solution and in the X-ray range at the Co K-edge in single crystals. The surprising absence of detectable X-ray magnetic circular dichroism or X-ray magnetochiral dichroism signals at the Co K-edge, even at low temperature (3 K) and a high magnetic field (17 T), is ascribed to a strongly delocalized spin density on the tricobalt core.